VIDA DE MACRINA: SANTIDADE, VIRGINDADE E ASCETISMO FEMININO CRISTÃO NA ÁSIA MENOR DO SÉCULO IV - da Costa, Ricardo; Zierer, Adriana (PHOÎNIX, 2020)
This paper intends to analyse the concept of santity, feminine ascetism and the importance of virginity to Christianism in the fourth century. In Life of Macrina, written by her brother Gregory of Nyssa, we can see the saint through the eyes of a man and her role in early Christianism in Capadocia, Asia Minor. He describes her influence over her brothers, three of which are known to be the capadocian fathers: Basil of Cesarea, Gregory of Nyssa and Peter of Sebastea. All of them fought against arianism. Macrina had great importance in leaing her brothers to the christian faith, her role as a virgin helped to mantain the purity of christianism at her time since her great latowlegde was based in the Sriptures and in the writings of the Church Fathers, She also created a convent which greatly influenced Basil, who is the father of oriental monasticism. Also, we can see in Gregory s work other aspects that contributed to her santity: her miracles. It is also very relevant Macrina's relationship with her mother Emelia, who also joined her in the convent.